2014
DOI: 10.2174/1389201015666140528152138
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Indigenously Isolated Fungi for Lovastatin Production and Its in vivo Evaluation

Abstract: Seven indigenously isolated fungal strains (Aspergillus niger, Aspergillus flavus, Aspergillus terreus, Penicillium citrinum, Penicillium notatum, Pleurotus ostreatus and Trichoderma viradae) were tested for their potential to produce cholesterol lowering drug lovastatin by using different agro-industrial wastes (Corn cobs, corn stover, banana stalk, wheat straw, wheat bran, bagasse) in submerged as well as solid state fermentation. Aspergillus terreus showed maximum production of 18.74 mg/100 mL by wheat bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Processed cocoa beans contain over 500 identifiable organic substances [ 21 , 23 ] derived from cocoa beans as well as bacterial and fungal species participating in cocoa bean fermentation. However, a significant majority of attempts to establish a causative relationship between the health benefits of cocoa-derived products and the chemical identity of cocoa bioactives are focused on substances originating exclusively from the cocoa bean cotyledons such as soluble phenolic compounds, insoluble polymeric phenolics, and methylxanthines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Processed cocoa beans contain over 500 identifiable organic substances [ 21 , 23 ] derived from cocoa beans as well as bacterial and fungal species participating in cocoa bean fermentation. However, a significant majority of attempts to establish a causative relationship between the health benefits of cocoa-derived products and the chemical identity of cocoa bioactives are focused on substances originating exclusively from the cocoa bean cotyledons such as soluble phenolic compounds, insoluble polymeric phenolics, and methylxanthines.…”
Section: Discussionmentioning
confidence: 99%
“…As shown recently, Penicillium citrinum , a major type of fungi identifiable in fermented cocoa beans, produces a novel thermostable alkaloid, Penicitrinine A, which displays significant antitumor and antimetastatic activities [ 20 ]. According to other recent reports, Penicillium citrinum , as well as some members of the Aspergillus family, may synthesize substantial amounts of lovastatin, a powerful inhibitor of cholesterol biosynthesis [ 21 ]. Moreover, some isolates of Penicillium citrinum have lately been shown to produce some metabolites with significant antibacterial and antifungal activity [ 22 ].…”
Section: Fungal Metabolitesmentioning
confidence: 99%
“…Hussein and Brasel (2001); Pusztahelyi et al (2015), noted that fungal secondary metabolic products contain compounds that have a high affinity for the mitochondrial membrane causing a rapid crash and also inhibit the protein transport chain, this inhibition may lead to a reducing in the production of energy that required to synthesize cholesterol. Also, Javed et al (2014) found that seven indigenously of Aspergillus strains were able to produce cholesterol-lowering drug lovastatin, and the Aspergillus terreus strain showed maximum production, the optimized lovastatin was extracted from fermented broth and orally administered to rats. It was concluded that fermented lovastatin effectively lowers the cholesterol level of rats, while Rashid et al (2013) found that the highest lovastatin production was produced by Aspergillus niger SAR strain.…”
Section: Effect On Glucose and Cholesterol Levelmentioning
confidence: 99%
“…These drugs are competitive inhibitors of hydroxymethylglutaryl-CoA reductase (HMG-CoA; EC 1.1.1.88), which catalyzes the rate-limiting step of the isoprenoid biosynthesis pathway associated with the production of cholesterol in humans and ergosterol in fungi [2]. In nature, LOV is produced by fungi from various taxonomic groups, for example, Ascomycetes, Aspergillus, Doratomyces, Gymnoascus, Hypomyces, Monascus, Paecilomyces, Penicillium, Phoma, Trichderma or basidiomycetes Lenzites, Omphalotus, Phanerochaete, Pleurotus, Trametes and many others [3][4][5]. Since, in fungi, this secondary metabolite (SM) inhibits the biosynthesis of ergosterol, which is necessary for building the cytoplasmic membrane, the fungal LOV producers should be resistant themselves to it [6,7].…”
Section: Introductionmentioning
confidence: 99%